Bunge’s systemic approach: An epistemological approach to the analysis of education - Ramos Ramos, Cristian Yosimar (2023)
This paper aims to examine Bunge’s fundamental contribution to systemic theory and propose a theoretical extension using Elster’s theory of rational action, basically incorporating his mixed (causal-intentional) or interactionist explanation. The answer will be a theoretical synthesis that will allow us to explain the complex interactions, provided that all rational action works within a system.